Synonymous terms in Lithuanian works of literary science in 1918–1940 - Mitkevičienė, Asta (Lietuvių kalba, 2015)
The article deals with synonymous terms used in the works of the theory and history of literary science published in Lithuanian between 1918 and 1940 (i.e. period of independent Lithuania). The paper discusses extent of terminology synonymy, types of one-word synonyms according to root of terms and their origin, identifies the fate of synonymous terms. The work follows the opposition principle. Synonymy is characteristic to literary terminology of aforesaid time (about 40% one-word terms have one-word synonyms). That proves terminological statement, that synonymy is typical to the first stages of development of terminology in particular domain. Besides terms have been extracted from texts and that might determine greater amount of synonymy and other variation of terminology. Since the better part of sources investigated is textbooks and other works for learning/studies, the reason for some synonyms (especially international) might be a didactic one. Synonymic relations link co-rooted terms (48% of the lines of synonyms), not co-rooted terms (37%) as well as mixed ones (15%). Lines of synonyms comprise of Lithuanian synonyms and synonyms with borrowed root (mostly international one) (38%), only Lithuanian-origin synonyms (36%) or synonyms with borrowed root alone (26%). In accordance with the number of sources, international terms and hybrids with international root not always overtake Lithuanian synonyms. Besides some of the first ones have more than one Lithuanian synonym. From international and Lithuanian synonyms now in some cases international terms are used, in other cases – Lithuanian synonyms or both Lithuanian and international terms. Several former international and Lithuanian synonyms have different meanings at present. Lithuanian-origin synonyms reflect realized possibilities for terminologization and term formation. Words that were terminologizated, in general lexis had synonyms, the same with underlying words of terms derivatives. That is a linguistic reason for some synonymous terms. Surely, some terms of lines of synonyms were used just in one source, but there are terms among them that have remained. Usually the synonym that was used in a greater number of the sources (as well as in the sources of the thirties) has entrenched. An attempt to differentiate meanings of some synonyms is observable in the period investigated. From the side of regulation of terminology, synonymous terms investigated are both the reason for terminology harmonization (efforts to find best terms) and the result of it (a few terms naming one concept for the time being particularly in different sources). Some synonyms might occur due to attempt to avoid polysemy of terms.